2014
DOI: 10.1016/j.jvs.2014.03.282
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the impact of open and endovascular abdominal aortic aneurysm repair on renal function

Abstract: OR and suprarenal fixation EVAR are associated with significant declines in renal function during 2 years, in contrast to infrarenal EVAR fixation. The patterns of eGFR decline in OR and suprarenal fixation EVAR are not similar, suggesting different causal mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
0
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 38 publications
0
28
0
2
Order By: Relevance
“…Overall, immediate post-operative renal injury, using absolute SCr drop within 48 hours, has a lower incidence post-EVAR compared to open-repair in most historical series, 32 whereas at least 3 studies (2 of which defined "AKI" as SCr rise> 50% and one as >30% compared to baseline) have shown increased incidence following EVAR (estimated at about 18%) than open repair (ranging from 5% to 15%). 4,6,28,[33][34][35] The introduction and evolution of contemporary criteria for AKI definition [Risk Injury Failure Loss End-stage (RIFLE), Acute Kidney Injury Network (AKIN), and Kidney Disease Improving Global Outcomes (KDIGO)] 36 has provided a uniform basis for research efforts in the field and led to conduction of several relevant studies. Table 1 summarizes findings of studies reporting AKI incidence after elective EVAR, using contemporary AKI reporting criteria.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, immediate post-operative renal injury, using absolute SCr drop within 48 hours, has a lower incidence post-EVAR compared to open-repair in most historical series, 32 whereas at least 3 studies (2 of which defined "AKI" as SCr rise> 50% and one as >30% compared to baseline) have shown increased incidence following EVAR (estimated at about 18%) than open repair (ranging from 5% to 15%). 4,6,28,[33][34][35] The introduction and evolution of contemporary criteria for AKI definition [Risk Injury Failure Loss End-stage (RIFLE), Acute Kidney Injury Network (AKIN), and Kidney Disease Improving Global Outcomes (KDIGO)] 36 has provided a uniform basis for research efforts in the field and led to conduction of several relevant studies. Table 1 summarizes findings of studies reporting AKI incidence after elective EVAR, using contemporary AKI reporting criteria.…”
Section: Introductionmentioning
confidence: 99%
“…Elective treatment in the form of open (OAR) or endovascular (EVAR) repair is advocated in those with an AAA of more than 5.5cm in diameter (30). Both OAR and EVAR can lead to significant renal insults (31). We have previously shown that almost 20% of patients undergoing elective EVAR will develop AKI and that is associated with impaired short and long-term outcomes (1,4,14).…”
Section: Introductionmentioning
confidence: 99%
“…The current prevalence of AAA for men above the age of 65 ranges from 2 to 7%, and elective treatment in the form of open or endovascular repair (OAR or EVAR) is advocated when the AAA-diameter reaches 5.5 cm [8] . Both OAR and EVAR can lead to significant insults to the kidney, such as hypovolaemia, ischaemia-reperfusion injury, and contrast nephropathy [7,9] . EVAR is associated with better short-term results compared to OAR; however, this benefit is not sustained after the third postoperative year [10][11][12] .…”
Section: Introductionmentioning
confidence: 99%